2018
DOI: 10.1111/nph.15124
|View full text |Cite
|
Sign up to set email alerts
|

In situ warming in the Antarctic: effects on growth and photosynthesis in Antarctic vascular plants

Abstract: The Antarctic Peninsula has experienced a rapid warming in the last decades. Although recent climatic evidence supports a new tendency towards stabilization of temperatures, the impacts on the biosphere, and specifically on Antarctic plant species, remain unclear. We evaluated the in situ warming effects on photosynthesis, including the underlying diffusive, biochemical and anatomical determinants, and the relative growth of two Antarctic vascular species, Colobanthus quitensis and Deschampsia antarctica, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 68 publications
3
70
0
Order By: Relevance
“…We found that the etiolation of warmed S. medium capitula seemed to have hampered its ability to increase its photosynthesis. The shrinkage of capitula may have triggered specific adjustments in the leaf anatomical determinants of CO 2 fixation and/or transfer (Sáez, Cavieres, & Galmés, ), limiting photosynthetic CO 2 assimilation of S. medium under higher temperatures. Ultimately, although the exact mechanisms are unclear, our results suggest that S. medium has a lower phenotypic and functional plasticity than S. fallax and as such is unable to adapt its morphology to cope with rising temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the etiolation of warmed S. medium capitula seemed to have hampered its ability to increase its photosynthesis. The shrinkage of capitula may have triggered specific adjustments in the leaf anatomical determinants of CO 2 fixation and/or transfer (Sáez, Cavieres, & Galmés, ), limiting photosynthetic CO 2 assimilation of S. medium under higher temperatures. Ultimately, although the exact mechanisms are unclear, our results suggest that S. medium has a lower phenotypic and functional plasticity than S. fallax and as such is unable to adapt its morphology to cope with rising temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported that both Antarctic species respond differentially to the in situ diurnal warming (Sáez et al ). Nevertheless, to the best of our knowledge, our study is the first one analyzing the effect of nocturnal warming on respiration and photosynthesis in both Antarctic vascular species.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf temperature records taken in this study site during the summer showed that in both species leaf temperature during the day is on average 5 to 8°C, with a maximum of ca. 10°C, and decreasing to 0 to 2°C during the night (Sáez et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only two native vascular plants of Antarctica (Figure c) have been extensively studied in terms of temperature, water availability and nutrient deficiency (Sáez et al , , ,b; Clemente‐Moreno et al , , ). Interestingly, for both species, g m is the most important limitation under low temperature, drought and nutrient deficiency, as has been previously reported for species from semiarid‐arid environments (Galmés et al , ).…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 99%